Implementation of Siemens S7-1200 PID Control on Festo Labvolt 3531 Plant Level Controller with Topkapi SCADA Using Modbus Communication Protocol - Supriyanto, Hadi; Rizal, Muhammad Nursyam; Wibowo, Sugeng (Journal La Multiapp, 2024)
Plant Festo LabVolt 3531 is a DCS, SCADA and process control system trainer based on the Allen Bradley Controllogix 5572 PLC and Factorytalk View SCADA. This research aims to provide another controller solution that can be used on the Festo Labvolt 3531 plant besides the Allen Bradley Controllogix 5572 PLC and FactoryTalk View SCADA. So that students have alternatives and variations of other technologies in learning. In this research, the Siemens S7-1200 PLC was used as a replacement for the Allen Bradley Controllogix 5572 PLC and Topkapi SCADA as a replacement for FactoryTalk View SCADA. As validation of the test, PID control was used to regulate the water level in both tubes at the Festo Labvolt 3531 plant. The test results for several specified height levels showed that the Siemens S7-1200 PLC with PID control integrated into Topkapi SCADA using the mobus communication protocol was successfully implemented , where the resulting control response has an average steady-state error of less than 2% and the delay between the interface and the device on the plant is 0s.